Seasonal plasticity in photoprotection modulates UV‐induced hsp gene expression in copepods from a clear lake - Tartarotti, B. (Limnol Oceanogr, 2018)
Zooplankton from clear alpine lakes is exposed to stressful levels of solar UV radiation (UVR). As these pelagic organisms experience high UVR and large changes in solar radiation conditions between ice‐free and ice‐cover periods, they have evolved various strategies to minimize UVR exposure and damage. Here, we studied the relation between photoprotection levels (mycosporine‐like amino acids, carotenoids), antioxidant capacities, and gene expression of heat shock proteins (hsps) as indicator of stress in the copepod Cyclops abyssorum tatricus during the course of a year. Expression of hsp60, hsp70, and hsp90 was measured in the field (baseline expression [BE]) and after UVR exposure in the laboratory. The BE differed among genes and seasons (hsp60: high during summer, hsp70 and hsp90: high during the ice‐cover period). The gene expression of hsp70 was upregulated after exposure to UVR (up to 5.2‐fold change), while hsp60 and hsp90 were only constitutively expressed. A strong seasonal pattern was found in the photoprotective compounds and antioxidant capacities, with highest levels during the ice‐free period. The extent of upregulation of hsp70 gene expression increased with decreasing photoprotection levels and peaked 24 h post UVR exposure (9.6‐fold change) at the time of lowest photoprotection (February). Our data suggest that hsp70 gene expression is modulated by seasonal plasticity in photoprotection. This ability of adequate stress response is essential for survival in highly variable ecosystems such as alpine lakes.